Dificuldades no cumprimento das boas práticas de transparência online: um estudo de caso dos municípios do COREDE – Fronteira Oeste - (:unkn) unknown (Universidade Federal do Pampa, 2015)
With the evolution of the Internet and digital technologies emerged the information society, where people want to participate, give opinions, control public spending and could change the course of policy. The government also had need to use Information and Communication Technologies to provide information and transparency that society is entitled. The use of these technologies in the public service is called e-government and it was possible to provide more information and provide more services. The main channel for this interaction between citizens and government are the portals of transparency, where every public agency must have a portal and contain the information that the legislation asks. The objective of this study is to show the importance of the issue and identify the difficulties faced by municipalities in COREDE Fronteira Oeste to meet the good transparency practices on the Internet, since most government agencies do not have portals with clear and organized information and many if you want to have all the necessary information. The survey brings some reflections on the information society, e-government portals and transparency, it is possible to visualize how did this need for transparency and its importance. To meet the objective was applied a qualitative research taking as north a previous document analysis on the Prize Report of Good Transparency Practices on the Internet Performed by the TCE in 2014 and observation at the gates of the cities chosen for the study, which will be the municipalities that are part of the Council Regional of Rio Grande do Sul Development (COREDE) Fronteira Oeste. After these data collections was applied an interview with those responsible for supervising the information portals of municipalities, from the analysis of the data, obtained a clearer view of the difficulties faced with the implementation of transparency in portals such as failure to communicate between sectors, provide documents in various formats, lack of interest of managers, lack of a sector responsible for the transparency portal, internal bureaucracy, political interest, among other factors. It was also observed that larger municipalities are recording growth, although slow, but small municipalities still do not give due importance to the portal, getting the mercy of the private company that is not properly monitored and has its properly defined responsibilities. And with that we can also point out some initiatives of municipalities that have managed to overcome these difficulties and win the prize Good Transparency Practices on the Internet.
Keywords: Portal of transparency; Public management: Brazil: Rio Grande do Sul: Santana do Livramento; E-government; Public Administration: ICT; CNPQ::CIENCIAS HUMANAS; Gestão pública: Brasil: Rio Grande do Sul: Santana do Livramento; Portal da transparência; Governo eletrônico; Administração pública: TIC